The Effect of Celebrity Endorsement on Purchase Decisions with Brand Awareness and Purchase Intention as Intervening Variables (Survey of “Bestcorn” Consumers, Bulukumba, South Sulawesi) - Rahmat Taufiq; Edy Yulianto; Swasta Priambada (Jurnal Mamangan, 2024)
This research is motivated by the fluctuation of "BestCorn" product sales despite implementing a celebrity endorsement strategy, as well as the inconsistency of findings in previous studies regarding the role of brand awareness. The purpose of this study is to analyze the influence of celebrity endorsements on purchasing decisions by examining the role of brand awareness and purchase intention as intervening variables. This study uses a quantitative causal method, where data were collected through questionnaires from 120 "BestCorn" consumers in Bulukumba selected using purposive sampling techniques and analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The results show that celebrity endorsements have a positive and significant effect on brand awareness, purchase intention, and purchase decision. In addition, brand awareness and purchase intention were also found to have a positive and significant effect on purchase decisions. The main findings revealed that brand awareness and purchase intention were proven to significantly mediate the relationship between celebrity endorsements and purchase decisions. In conclusion, celebrity endorsements influence consumer purchasing decisions not only directly, but also indirectly through strengthening cognitive (brand awareness) and affective (purchase intention) pathways.